The role of day one postoperative review of intraocular pressure in modern vitrectomy surgery. Issue 9 (20th January 2017) - Brennan, Nicholas; Reekie, Ian; Ezra, Eric; Barton, Keith; Viswanathan, Ananth; Muqit, Mahiul MK
Abstract : Background: With the introduction of sutureless 23-gauge (23G) vitrectomy, the risks for elevated intraocular pressure (IOP) and the need for day 1 review of IOP are less certain. Aims: To assess current practice for postoperative review in the vitreoretinal service at a large tertiary referral centre; to assess whether day 1 review detected complications altering patient management; to identify risk factors for IOP spikes postvitrectomy. Methods: Retrospective, consecutive case note review of all patients undergoing 23G vitrectomy at the study institution between April and June 2013. Patients had assessment at either day 1, week 2 and month 2 or week 2 and month 2. Linear regression analysis was performed to identify risk factors for IOP elevation. Results: 200 (89%) cases met inclusion criteria. Of these, 176 (89.3%) had day 1 review, 24 (12%) were seen at week 2. Mean follow-up was 120 days (range 20–360). Two cases (1%) required urgent surgical intervention due to early IOP complications. Combined laser was the only risk factor for a day 1 IOP spike (p=0.005). In total, 44 patients (22%) were treated for elevated IOP within 2 weeks following vitrectomy. No long-term complications were detected in these patients. Conclusions: Day 1 review detected adverse events in 0.5% of study patients. No long-term complications were reported in the 22% of patients who received treatment for early postoperative IOP elevation. This observation has led to the removal of routine day 1 review from the surgical care pathway following routine uncomplicated vitrectomy at the study institution.